Characterization of Differential Protein Tethering at the Plasma Membrane in Response to Epidermal Growth Factor Signaling - Looyenga, Brendan D. (2012)
[Image: see text] Physical tethering of membrane proteins to the cortical actin cytoskeleton provides functional organization to the plasma membrane and contributes to diverse cellular processes including cell signaling, vesicular trafficking, endocytosis, and migration. For these processes to occur, membrane protein tethering must be dynamically regulated in response to environmental cues. In this study, we describe a novel biochemical scheme for isolating the complement of plasma membrane proteins that are physically tethered to the actin cytoskeleton. We utilized this method in combination with tandem liquid chromatography/mass spectrometry (LC–MS/MS) to demonstrate that cytoskeletal tethering of membrane proteins is acutely regulated by epidermal growth factor (EGF) in normal human kidney (HK2) cells. Our results indicate that several proteins known to be involved in EGF signaling, as well as other proteins not traditionally associated with this pathway, are tethered to the cytoskeleton in dynamic fashion. Further analysis of one hit from our proteomic survey, the receptor phosphotyrosine phosphatase PTPRS, revealed a correlation between cytoskeletal tethering and endosomal trafficking in response to EGF. This finding parallels previous indications that PTPRS is involved in the desensitization of EGFR and provides a potential mechanism to coordinate localization of these two membrane proteins in the same compartment upon EGFR activation.